Characterization of gas-liquid flows in rectangular bubble columns using conductivity probes - Buwa, Vivek V.; Ranade, Vivek V. (Chemical Engineering Communications, 2005)
Unsteady gas-liquid flows in bubble columns are comprised of various flow processes occurring with varying length and time scales and govern mixing and transport processes. In the present work, we have characterized dynamic and time-averaged properties of gas-liquid flows in rectangular bubble columns using conductivity probes. The development of a single-tip conductivity probe, data processing methodology, and photographic validation procedure is discussed in detail. The effect of superficial gas velocity and aerated liquid height-to-width ( H/W) ratio on voidage fluctuations and time-averaged gas holdup was investigated. The experimental data presented here can help in understanding the dynamics of various flow processes and validating computational fluid dynamics based models.
Keywords: Bubble column; gas holdup; gas-liquid flows; voidage fluctuations